PENGARUH PENERAPAN METODE LEAN CONSTRUCTION PADA BIAYA PEKERJAAN STRUKTUR TIPIKAL - Benediktus Warno Sitinjak; Yovi Arsianto; M. Agung Wibowo; Frida Kistiani (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2015)
Indonesian construction development of more advanced, making the competitiveness between the contractor becomes tight. Therefore, we need an innovation in managing the construction process becomes more optimal. One such innovation is the application of the lean construction method with work structuring concept. Work structuring concepts we use to design simulated a typical floor concrete structure work in order to have a more reliable flow of activities and faster. Innovation Lean Construction on this research using inter-floor transfer system formwork on horizontal PERI formwork. With the concept of structuring work, the interaction between the concrete structure of the work cycle and the cycle formwork transfer between floors design 3 simulation obtained optimal with a reliable stream of activity (minimum idle time) that simulated 3 days, 5 days and 9 days. From the calculation of total RAB optimal simulation of each project, the simulation of 3 days is the most optimal simulation.